A review of the efficacy of dietary polyphenols in experimental models of inflammatory bowel diseases. Issue 6 (10th June 2015) - Martin, Derek A.; Bolling, Bradley W.
<x xml:space="preserve">Abstract</x> The use of polyphenols in rodent models of inflammatory bowel diseases is reviewed. Many polyphenols inhibit colitis through multiple mechanisms, however higher doses of some treatments may exacerbate inflammation.